Acquired lymphangioma of the vulva – clinical and dermoscopic presentation - Sadko, Krzysztof; Płaszczyńska, Anna; Sławińska, Martyna; Konczalska, Monika; Sobjanek, Michal (Dermatology Review/Przegląd Dermatologiczny, 2022)
Acquired lymphangioma, also called acquired cutaneous lymphangiectasia or secondary lymphangioma, is a relatively rare and benign tumour consisting of dilated superficial lymphatic vessels. We present 50-year-old patient diagnosed with acquired lymphangioma of the vulva and discuss the diagnostic methods of the disease, including dermoscopy.